Methods of Teaching Creative Writing in High School: A Review of Recent Literature. - Maginnis, Mary (Loyola College, 2023)
This survey of literature discusses the content and research methodology of 25 articles on creative writing written since 1988. It is divided into sections covering articles discussing (1) definitions of creativity; (2) theoretical aspects of teaching creative writing; (3) specific teaching methods; (4) journal writing to discuss literature; and (5) how to plan a visiting author's program. The review, containing articles from journals and from ERIC, is weighted more heavily towards the areas of theory and poetry because more literature was available in those areas. Section 1 reviews articles by Gary Davis ("Portrait of the Creative Person) and Ron McFarlane ("An Apologia for Creative Writing"). Section 2 reviews articles by Nancy L. Reichart ("Defining and Refining Boundaries of the Creative Writing Workshop"), Lynn Domina ("The Radar O'Reiley School of Creative Writing"), Gayle Elliot ("The Angel in the Academy: The Creative Writer as Helpmeet on the Distaff Side of English Studies"), and Cecil Morris and Dana Haight ("A Funny Thing Happened When We Began to Write"). Section 3 reviews articles by Michael Bugeja ("Why We Stop Reading Poetry") , Diane Lockwood ("Poets on Teaching Poetry"), and Lynn McGee ("Finding the Poet in New Writers") Section 4 reviews articles by Nancy Hudson ("The Violence of Their Lives: The Journal Writing of Two Higll School Freshmen") and R. W. Burniske ("Creating Dialogue: Teacher Response to Journal Writing"); Section 5 reviews an article by Joseph Sanacore ("Supporting a Visiting Author's Program"). (Contains 25 references.)